2014
DOI: 10.3762/bjoc.10.82
|View full text |Cite
|
Sign up to set email alerts
|

Cuevaenes C–E: Three new triene carboxylic derivatives from Streptomyces sp. LZ35ΔgdmAI

Abstract: SummaryTwo pairs of geometrical isomers – cuevaenes A (1) and C (3) as well as cuevaenes D (4) and E (5) – and cuevaene B (2) were isolated from gdmAI-disrupted Streptomyces sp. LZ35. The constitution of cuevaene C (3) was found to be identical to cuevaene A (1) by means of NMR spectroscopy and high resolution mass spectrometry. However, the relative configurations of the triene side chain moieties were determined to be different. It was established on the basis of spectroscopic data that cuevaenes D (4) and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Cuevaenes A, obtained from gdmAI -disrupted Streptomyces sp. LZ35, exhibits antibacterial activity . (−)-Eupachinin B and its enantiomer, isolated from the roots of Eupatorium chinense , possess an unusual 1,2,3,4-tetrahydrodibenzo­[ b , d ]­furan skeleton .…”
mentioning
confidence: 99%
“…Cuevaenes A, obtained from gdmAI -disrupted Streptomyces sp. LZ35, exhibits antibacterial activity . (−)-Eupachinin B and its enantiomer, isolated from the roots of Eupatorium chinense , possess an unusual 1,2,3,4-tetrahydrodibenzo­[ b , d ]­furan skeleton .…”
mentioning
confidence: 99%
“…The cultivated strain of Streptomyces LZ35 produces cuevaenes A and C, cuevaenes D and E, and cuevaene B. Cuevaenes A-C displayed moderate activity against Bacillus subtilis and against fungi Fusarium verticillioides, and Rhizoctonia solani [154]. Cuevaenes A, C and cuevaene B contained unusual FA (136)(137)(138), respectively.…”
Section: No Predicted Biological Activity Pa *mentioning
confidence: 99%
“…CMB-M0232 obtained from a sediment sample near Brisbane, Australia is a producer of nocardiopsins A-D [166,167]. Nocardiopsins A and C contained FA (154), and nocardiopsins B and D contained FA (155). Two polyketide metabolites, thailandamide A and thailandamide lactone with (E)-7-hydroxy-8-(4-hydroxyphenyl)-2-methyloct-4-enoic acid (156) have been isolated from gram-negative bacillus Burkholderia thailandensis [168,169].…”
Section: No Predicted Biological Activity Pa *mentioning
confidence: 99%
“…201 produced 2-methylheptyl isonicotinate able to inhibit the growth of F. moniliforme more efficiently than a natural analogue (isoniazid) [98]. On the other hand, modest activity was observed by the metabolites extracted from Streptomyces LZ35 against F. verticillioides [104]. For several studies, chitinase activity, rather than antibiotic production, was shown to play a role in the antifungal mechanism [105][106][107][108].…”
Section: Evaluation Of Antifungal Mechanism Of Actionmentioning
confidence: 99%